Management and Islamic Leadership in the Himpunan Mahasiswa Islam (HMI) Organization in Padangsidimpuan City - Siregar, Ahmad Sofyan; Syafnan; Yolanda, Gabena; Aswar HARAHAP (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study aims to examine the implementation of Islamic management and leadership in the Himpunan Mahasiswa Islam (HMI) organization in Padangsidimpuan, focusing on organizational culture, leadership style, and change management. The research employs a qualitative approach through in-depth interviews, participant observation, and document study to collect data from the management, active members, and alumni. The findings show that HMI's organizational culture, based on Islamic values such as honesty, trustworthiness, consultation (musyawarah), and ukhuwah Islamiyah, plays a significant role in the formation of cadres with Islamic character. The consultation-based leadership style (syura) has proven effective in increasing member involvement and collective decision-making, although challenges such as apathy and differing viewpoints can slow down the process. Additionally, HMI's organizational management demonstrates good adaptability in facing changes through mechanisms such as monthly evaluation meetings and cadre training. This study concludes that the interaction between organizational culture, leadership style, and adaptive management is key to HMI's success in producing competent cadres who contribute to society.